Inhibition of Arp2/3 complex after ADP-ribosylation of Arp2 by binary clostridioides toxins - Schwan, Carsten; Lang, Alexander E.; Schlosser, Andreas; Fujita-Becker, Setsuko; AlHaj, Abdulatif; Schröder, Rasmus R.; Faix, Jan; Aktories, Klaus; Mannherz, Hans Georg (Cells, 2022)
Clostridioides bacteria are responsible for life threatening infections. Here, we show that in addition to actin, the binary toxins CDT, C2I, and Iota from Clostridioides difficile, botulinum, and perfrigens, respectively, ADP-ribosylate the actin-related protein Arp2 of Arp2/3 complex and its additional components ArpC1, ArpC2, and ArpC4/5. The Arp2/3 complex is composed of seven subunits and stimulates the formation of branched actin filament networks. This activity is inhibited after ADP-ribosylation of Arp2. Translocation of the ADP-ribosyltransferase component of CDT toxin into human colon carcinoma Caco2 cells led to ADP-ribosylation of cellular Arp2 and actin followed by a collapse of the lamellipodial extensions and F-actin network. Exposure of isolated mouse colon pieces to CDT toxin induced the dissolution of the enterocytes leading to luminal aggregation of cellular debris and the collapse of the mucosal organization. Thus, we identify the Arp2/3 complex as hitherto unknown target of clostridial ADP-ribosyltransferases.